2016
DOI: 10.1103/physrevb.94.201112
|View full text |Cite
|
Sign up to set email alerts
|

Drude weight fluctuations in many-body localized systems

Abstract: We numerically investigate the distribution of Drude weights $D$ of many-body states in disordered one-dimensional interacting electron systems across the transition to a many-body localized phase. Drude weights are proportional to the spectral curvatures induced by magnetic fluxes in mesoscopic rings. They offer a method to relate the transition to the many-body localized phase to transport properties. In the delocalized regime, we find that the Drude weight distribution at a fixed disorder configuration agre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 56 publications
5
44
1
Order By: Relevance
“…[23], the numerical results shown for the Many-Body-Localized phase are actually rather similar : on their Fig. 1, the heavy tail seems in reasonable agreement with the tail exponent of Eq.…”
Section: Many-body-localized Phase β =supporting
confidence: 72%
See 4 more Smart Citations
“…[23], the numerical results shown for the Many-Body-Localized phase are actually rather similar : on their Fig. 1, the heavy tail seems in reasonable agreement with the tail exponent of Eq.…”
Section: Many-body-localized Phase β =supporting
confidence: 72%
“…In Ref. [23], the authors have found numerically that the ergodic phase of the Many-BodyLocalization model is "in excellent agreement" non only with the tail of Eq. 25, but also with the RMT result of Eq.…”
Section: Statistical Properties Of the Dimensionless Curvature Kmentioning
confidence: 80%
See 3 more Smart Citations